Adolescent peer support for mental health problems: evaluation of the validity and reliability of the Mental Health Support Scale for Adolescents - Shurong Lu; Laura M. Hart; Anthony F. Jorm; Karen Gregg; Maxine Gross; Andrew J. Mackinnon; Amy J. Morgan (BMC Psychology, 2023)
Abstract Background The Mental Health Support Scale for Adolescents (MHSSA) is a criterion-referenced measure of adolescents’ supportive intentions towards peers with mental health problems, which was developed for use in evaluations of adolescent mental health interventions, such as the teen Mental Health First Aid (tMHFA) program. The present study aimed to examine the validity and reliability of the MHSSA. Methods A sample of 3092 school students (Mean ± SD: 15.9 ± 0.4 years old) and 65 tMHFA Instructors (the adult group with known expertise in tMHFA) completed the 12 items of the MHSSA. A sub-sample of 1201 students repeated the scale after a 3-4-week interval. Item concordance rates with the tMHFA Action Plan across helpful and harmful intentions scales were calculated. Scale reliabilities were assessed using agreement coefficients from a single test administration and test-retest reliability measured by intraclass correlation coefficients. The mean differences of MHSSA scores of students and Instructors were compared using independent samples t-tests, while convergent validity was tested via correlations of the scale with validated measures of confidence in providing help, social distance and personal stigma. Results The average score of Instructors was significantly higher than that of students. The scale was positively associated with confidence in providing help, whilst negatively associated with social distance and dimensions of personal stigma. All scales of MHSSA had high agreement coefficients (all > 0.80) and fair to good test-retest reliability over 3–4 weeks. Conclusions The MHSSA shows evidence of validity and reliability for use among adolescents for evaluating the quality of intentions to help peers with mental health problems.